Routinely Identifying frailty: Implementing the electronic Frailty Index in the Secure Anonymised Information Linkage Databank. (2018) - Hollinghurst, Joe; Akbari, Ashley; Rodgers, Sarah; Clegg, Andrew
No abstract available